2013
DOI: 10.1097/sap.0b013e31827eace2
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Antiadhesion Barriers in Hand Surgery

Abstract: Antiadhesion barriers are safe to use in humans for hand/wrist surgery. Studies to evaluate efficacy will require larger numbers of patients, but have already begun at our medical center. According to data from animal studies, antiadhesion barriers should serve as a useful tool for the decrease or even prevention of adhesion formation in the wrist and hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Patients recovered well and had good function. These promising results by Kohanzadeh et al 12 are very similar to our observations. We believe that the operative approach and the similar biological function of sodium hyaluronate with carboxymethylcellulose can explain our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients recovered well and had good function. These promising results by Kohanzadeh et al 12 are very similar to our observations. We believe that the operative approach and the similar biological function of sodium hyaluronate with carboxymethylcellulose can explain our findings.…”
Section: Discussionsupporting
confidence: 93%
“…We found one study that investigated the safety of Seprafilm. 12 The author reported no significant adverse effects. Patients recovered well and had good function.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous anti‐adhesion products have been introduced into the commercial market involving pharmacological inhibition and barrier prevention . However, none are composed of natural materials except hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies in animals have tended to prove that adhesion formation is decreased when applied locally or in combination with nonsteroidal anti-inflammatory drugs [29] or an amniotic membrane [25]. In 2013, Kohanzadeh et al [30] evaluated the efficacy of SEPRAFILM 1 (hyaluronic acid and methylcellulose) in 14 patients and found that it reduced adhesion formation. Nevertheless, no objective measurement of joint range of motion was reported.…”
Section: Pre-tenolysis At 6 Weeks At 3 Monthsmentioning
confidence: 97%